Erythromelalgia and Peripheral Nerve Block: A Case Report. Issue 8 (15th April 2019) - Lorello, Gianni R.; Perlas, Anahi
Abstract : A 79-year-old woman with primary erythromelalgia underwent a left reverse total shoulder arthroplasty with a left interscalene nerve block, a superficial cervical plexus block, and a general endotracheal anesthetic, with no residual neurological deficits. Herein, we discuss the classification and pathophysiology of erythromelalgia along with the anesthetic considerations of peripheral nerve blockade in patients with primary erythromelalgia.